2013
DOI: 10.4028/www.scientific.net/amr.668.767
|View full text |Cite
|
Sign up to set email alerts
|

Single Wafer Atomic Layer Deposition Reactor Design

Abstract: Atomic layer deposition (ALD) is a very attractive ultra-thin film deposition technique. With the feature size of IC industry continues going down, ALD has received more and more attentions for its accurate sub-nanometer thickness control as well as superior uniformity and conformality. The further development of ALD technology emphasizes on both process and equipment innovations. A single-wafer bottom-heated reactor is constructed successfully, and the Al2O3 is deposited with ~2% uniformity across a 4-inch wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Details on the parts considered are given in Tables S1 and S2. To create the inventory for ALD equipment, the size of the lab-scale reactor was obtained from the work of Zhou et al 31 A 3D model of the reactor was drawn, as shown in Figure 3, which was used to also estimate the weight of the reactor. The ALD equipment also required the inclusion of a vacuum pump.…”
Section: ■ Experimental Methodologymentioning
confidence: 99%
“…Details on the parts considered are given in Tables S1 and S2. To create the inventory for ALD equipment, the size of the lab-scale reactor was obtained from the work of Zhou et al 31 A 3D model of the reactor was drawn, as shown in Figure 3, which was used to also estimate the weight of the reactor. The ALD equipment also required the inclusion of a vacuum pump.…”
Section: ■ Experimental Methodologymentioning
confidence: 99%